Numerical study of flow establishment process of engine in a shock tunnel. (April 2023) - Zhang, Dongqing; Deng, Weixin; Xing, Jianwen; Zhou, Zheng
Abstract: In this paper, an unsteady numerical simulation of the full-scale flow field establishment process of a scramjet in shock tunnel is carried out. The simulation covers from the driving process of the shock tube to the flow field establishment of nozzle and engine, and combines the chemical reaction of air. The feasibility of the calculation method is verified by comparing the pressure from simulation results and the experimental ones that measured in the shock tube. The results show that in the shock tube, the total pressure at the nozzle inlet is formed by the incident shock wave, the shock wave reflected by the diaphragm and the shock wave train caused by the nozzle high pressure. After the nozzle flow field is established, the Mach number of the core flow reaches the design value of 9.0, and the total pressure of the core flow reaches 30 MPa. By comparing the results of flow fields, wall pressure distributions and drag coefficients with the steady case, we show that the flow in test section approaches steady state in 16 ms, which includes the shock tunnel and nozzle starting time. The non-dimensional characteristic establishment time of the engine is about 4 and it is closed to that of the flat plate case. Highlights: Unsteady simulation of an engine flow field establishment is carried out. Evolutions of the flow field and wave system are revealed. Non-dimensional characteristic establishment time of the engine is confirmed.